2021
DOI: 10.1021/acssuschemeng.1c04957
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Transfer Hydrogenation of Glucose to Sorbitol with Raney Ni Catalysts Using Biomass-Derived Diols as Hydrogen Donors

Abstract: The catalytic transfer hydrogenation (CTH) of glucose to sorbitol has been studied using a wide collection of different biomass-derived alcohols and diols as hydrogen donors. Catalytic activity results reflect the feasibility to conduct this transformation in the presence of conventional, commercially available Raney Ni-type sponges as catalysts. Sacrificial diols displayed a superior performance as hydrogen donors as compared to short-chain alcohols, including secondary alcohols. Among them, terminal diols su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The deactivation was presumably caused by the oxidation of the catalyst during recycling procedures (air exposure), which may be effectively avoided if a continuous-flow reactor was applied instead (not discussed here) or by slightly increasing the reaction temperature to 140 °C (83 % yield was obtained; Table 2, entry 16). The reduction of the recovered skeletal catalysts with H 2 or NaBH 4 were also investigated to regenerate the catalyst's reactivity; unfortunately, the results turned out to be disappointing as only 16 and 39 % BHMF yield were obtained, respectively. These results further indicated the distinct property of the skeletal catalysts from traditional supported metal catalysts.…”
Section: Catalytic Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The deactivation was presumably caused by the oxidation of the catalyst during recycling procedures (air exposure), which may be effectively avoided if a continuous-flow reactor was applied instead (not discussed here) or by slightly increasing the reaction temperature to 140 °C (83 % yield was obtained; Table 2, entry 16). The reduction of the recovered skeletal catalysts with H 2 or NaBH 4 were also investigated to regenerate the catalyst's reactivity; unfortunately, the results turned out to be disappointing as only 16 and 39 % BHMF yield were obtained, respectively. These results further indicated the distinct property of the skeletal catalysts from traditional supported metal catalysts.…”
Section: Catalytic Performancementioning
confidence: 99%
“…Catalytic transfer hydrogenation (CTH) is definitely an appealing candidate that has long been developed by sacrificing the H atoms from hydrogen source for hydrogenation. [16] Representative hydrogen sources are alcohols, [17] silanes, [18] and formic acid, [19] among which alcohols are the most frequently used ones featuring good reactivities, cost-effectiveness, and pH-neutrality. For example, a secondary alcohol, isopropanol (i-PrOH), has been well acknowledged with good reactivity in the CTH reaction; in particular, it can promote the HMF-to-BHMF conversion in the presence of Ru/Co 3 O 4 , [20] Co 3 O 4 @MC, [21] or Zr-DTPA [22] (MC = mesoporous carbon, DTAP = diethylenetriaminepentaacetic acid) catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that as the catalysis increased in the presence of NaHSO 3 co-catalyst under visible light irradiation conditions, and the % conversion yield of these products was improved. [4][5][6] From the aforementioned results, it was noted that Ag/AgBr/ g-C 3 N 4 nanocomposites were effective catalysts for hydrogenation reaction under visible light conditions at a concentration of 100 ppm after 8 h under ambient conditions (Table 3, entry 9). Whereas by adding higher concentrations of nanocatalyst at 150 ppm or 200 ppm, there were no observed changes in the % conversion of sorbitol (Table 3, entries 10 and 11).…”
Section: Studying the Effects Of Photonanoctaysts On The Hydrogenatio...mentioning
confidence: 97%
“…3 Recent studies have demonstrated the direct synthesis of sorbitol. [4][5][6] It was shown that high selectivity for the production of D-sorbitol was obtained when RANEY s Ni catalysts, in the presence of diols as hydrogen donors were used after 550 h. 4 In another study, the % conversion to sorbitol was 99% glucose conversion at 140 1C in 150 min reaction time when tannic acid-based porous carbon spheres supported Ni-Ru bimetallic catalysts. 5 Again, the potential effect of RANEY s nickel in the catalytic transfer hydrogenation reaction for the reduction of glucose to sorbitol proceeded at elevated temperatures (130-190 1C) after 6 h. 6 This work aims to explore an alternative reaction pathway for the transformation of glucose into sorbitol by exploring the feasibility of photocatalysis without the use of H 2 gas under pressure.…”
Section: Introductionmentioning
confidence: 99%